FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI MASYARAKAT DESA MUARA BARU KECAMATAN SUNGAI RAYA - Febbyanti, Tari; Asriati, Nuraini; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research was to determine the factors that affect of economic growth at Muara Baru Village. The research method that used in this research was descriptive study with a form of qualitative research. The data that used in this research was primary and secondary data. The data collection that used in this research was observation, interview, and documentation while the data analysis technique using domain analysis technique. The result of this result showed that there were a factor that influenced the economic growth of Muara Baru Village. The result showed that (1) the land and other natural wealth of 3.18 were categorized as quite good. (2) the amount and quality of population and labor of 3.00 were categorized as good enough. (3) the capital goods and technology level of 2.6 were categorized as good. (4) the social system and community attitude of 4.00 were categorized as strong.Keywords: Economic Growth, Society in The Village , GNPÂ